The Impact of Russia and Ukraine War on Global Food Insecurity - Utami, Rahmadini Agung Ayu; Maliki, Musa (Jurusan Ilmu Hubungan Internasional, 2024)
Conflict plays a major role in famine as 60 percent of the world's hungry people come from conflict and violence-prone areas. The current conflict between Russia and Ukraine is a clear example of the relationship between conflict and food crisis. The conflict between Russia and Ukraine is not only causing hunger for Ukrainians, but also for people in other countries. Conflicts involving the largest food supply countries have a direct impact on global food distribution. This research aims to examine the impact of the Russia-Ukraine war on global food insecurity using a qualitative-descriptive method. Data were collected using literature study technique with the help of secondary data. The results of this study show that the food insecurity caused by the war in Russia and Ukraine also has an impact on the price of goods in a number of countries. The interruption of supplies from Russia and Ukraine hampered the supply chain of food commodities and other agricultural products. As a result, the prices of these other types of products have increased. In fact, food insecurity can also have an indirect impact on increasing the country's foreign debt.